Mapping Adverse Drug Reactions burden in Mono- and Dual-Antiplatelet Therapy: A Prospective Hospital-Based Study in CAD Patients - Reddy, Mandati Santhosh; Ganachari, Madiwalayya Shivakantayya (International Journal of Pharmaceutical Investigation, 2026)
Background Antiplatelet therapy is central to managing Coronary Artery Disease (CAD), but benefits are offset by Adverse Drug Reactions (ADRs), particularly bleeding. Objectives To compare the causality, severity, and preventability of ADRs associated with mono- and dual-antiplatelet therapy among hospitalized CAD patients. Materials and Methods A six-month prospective observational study in a tertiary care hospital included adult CAD patients on MAPT or DAPT. ADRs were identified via interviews and record reviews, then assessed using WHO-UMC, Hartwig-Siegel, and standard preventability tools. Data were analyzed using SPSS 26.0. Results Of 252 patients, 179 ADRs were found (125 in DAPT; 54 in MAPT). Gastrointestinal bleeding was most common. Intracranial hemorrhage and ticagrelor-induced dyspnea were more frequent with DAPT. DAPT ADRs more often required drug withdrawal or dose modification. Conclusion DAPT has a significantly higher ADR burden than monotherapy. Many ADRs are preventable, highlighting the need for individualized selection and vigilant monitoring.
Keywords: Adverse drug reactions; Antiplatelet therapy; Bleeding; Coronary artery disease; Dual antiplatelet therapy; Pharmacovigilance